Comparison of mortality between open and closed pelvic bone fractures in Korea using 1:2 propensity score matching: a single-center retrospective study - Jaeri Yoo; Donghwan Choi; Byung Hee Kang (Journal of Trauma and Injury)
Purpose Open pelvic bone fractures are relatively rare and are considered more severe than closed fractures. This study aimed to compare the clinical outcomes of open and closed severe pelvic bone fractures. Methods Patients with severe pelvic bone fractures (pelvic Abbreviated Injury Scale score, ≥4) admitted at a single level I trauma center between 2016 and 2020 were retrospectively analyzed. Patients aged <16 years and those with incomplete medical records were excluded from the study. The patients were divided into open and closed fracture groups, and their demographics, treatment, and clinical outcomes were compared before and after 1:2 propensity score matching. Results Of the 321 patients, 24 were in the open fracture group and 297 were in the closed fracture group. The open fracture group had more infections (37.5% vs. 5.7%, P<0.001) and longer stays in the intensive care unit (median 11 days, interquartile range [IQR] 6–30 days vs. median 5 days, IQR 2–13 days; P=0.005), but mortality did not show a statistically significant difference (20.8% vs. 15.5%, P=0.559) before matching. After 1:2 propensity score matching, the infection rate was significantly higher in the open fracture group (37.5% vs. 6.3%, P=0.002), whereas the length of intensive care unit stay (median 11 days, IQR 6–30 days vs. median 8 days, IQR 4–19 days; P=0.312) and mortality (20.8% vs. 27.1%, P=0.564) were not significantly different. Conclusions The open pelvic fracture group had more infections than the closed pelvic fracture group, but mortality was not significantly different. Aggressive treatment of pelvic bone fractures is important regardless of the fracture type, and efforts to reduce infection are important in open pelvic bone fractures.